Investigation of the radiation-thermal oxidation of beryllium in the system Be-water by the methods of infrared and optical spectroscopy - Gadzhieva, N.N.; Nurmammadova, F.N.; Melikova, S.Z. (Problems of Atomic Science and Technology, 2023)
Radiation-thermal oxidation of beryllium in contact with water at temperatures T = 473…773 K under the combined effect of temperature and gamma radiation has been studied by methods of infrared and optical spectroscopy. The formations of an oxide layer on the surface of beryllium were traced from the infrared and optical reflection spectra. In the IR spectra, the broadening of the oxide layer on the Be surface (T = 573 K) was revealed with an increase in the absorbed dose by ∼ 2.5 times, which is associated with inhomogeneities caused by gamma irradiation. According to the optical reflection spectra of the surface of radiation-thermally oxidized Be, it was revealed that in the region of the edge of short waves λ ≤ 250 nm, an absorption band is observed, the intensity of which increases with increasing contact time and indicates the formation of an oxide layer. Методами інфрачервоної (ІЧ) та оптичної спектроскопії досліджено радіаційно-термічне окислення берилію в контакті з водою при температурах Т = 473…773 К і сумісній дії температури та гамма-випромінювання. За інфрачервоним та оптичним спектрами відбиття простежено утворення оксидного шару на поверхні берилію. В ІЧ-спектрах виявлено розширення оксидного шару на поверхні Be (T = 573 K) при збільшенні поглиненої дози в ∼ 2,5 рази, що пов’язано з неоднорідностями, викликаними гамма-опроміненням. За даними спектрів оптичного відбиття поверхні радіаційно-термічно окисленого Be виявлено, що в області краю коротких хвиль λ ≤ 250 нм спостерігається смуга поглинання, інтенсивність якої зростає зі збільшенням часу контакту та вказує на утворення оксидного шару.